DESIGN CONTRIBUTIONS TO ADOPT MEDITERRANEAN DIET. CASE STUDY ORANGES FROM SILVES - Pias, Filipa (Journal of Tourism, Sustainability and Well-being, 2018)
The Mediterranean diet, considered Intangible Cultural Heritage by UNESCO in 2013, represents a complete and balanced food model with numerous benefits for health, longevity and quality of life, it is characterized by the consumption of fresh produce and of the time, by the frugality, simplicity and sharing a meal. Despite being a small farmer, Portugal can bet on cultural diversification and differentiation arising from the intrinsic quality of these products allowed by the unique climate and soil conditions. Due to its work process design, can collaborate with the company, it can draw solutions with and for the people, taking into account technical, environmental and economic constraints associated. Through design we can develop partnerships, complement the offering, create educational activities to community, develop a narrative that shows that behind the products there is a history, a way of being and draw an experience based on the nutritional value of the offer and the recommendation of the Mediterranean Diet Pyramid. We purpose a model that allows Portuguese agro-food SMEs to evaluate the collaboration of design. The model builds a narrative that has underlying the motivation and values which are at the origin of the product and the company and it allows designing an experience based on the nutritional value of the product and the recommendation of the Mediterranean Diet Pyramid to improve healthy eating habits or focus on a subject where the food has a decisive role. Silves town is applying the design evaluation model in investment in the new brand - “Silves, capital da laranja”. Its goal is to give notoriety to orange and producers in that region by associating to the name of Silves, recognized for its tangible and intangible heritage, and to the quality and accuracy with which orange is produced.